Epidemiology of pediatric trauma and its pattern in urban India: A tertiary care hospital-based experience - Vijay Kumar Kundal; Pinaki Ranjan Debnath; Amita Sen (Wolters Kluwer Medknow Publications, 2017)
Aim: To assess the epidemiology, pattern, and outcome of trauma in pediatric population. Materials and Methods: A total of 1148 pediatric patients below 15 years of age presenting in the emergency department of our hospital were studied over a period of 3 years. The patients were categorized into four age groups of <1 year, 1-5 years, 6-10 years, and 11-15 years. The data were compared regarding mode of trauma, type of injury, place of injury among different age groups and both sexes. Results: The majority of the pediatric trauma cases were seen in males 69.86%, (n = 802) and females comprised only 30.13% (n = 346). Road traffic accident (RTA) was the most common mode of trauma in male children, i.e. 59.47% (n = 477) followed by fall injuries, i.e. 29.42% (n = 236). In females, fall was the most common mode of trauma, i.e. 52.31% (n = 181) followed by RTA (36.70%, n = 127). Fall injuries occurred mostly at homes. Among RTA, hit by vehicle on road while playing was most common followed by passenger accidents on two wheelers, followed by hit by vehicle while walking to school. Among fall, fall while playing at home was the most common. Out of total 1148 patients, 304 (26.48%) comprised the polytrauma cases (involvement of more than two organ systems), followed by abdominal/pelvic trauma (20.99%, n = 241), followed by head/face trauma (19.86%, n = 228). Out of total 1148 patients admitted over a period of 36 months, 64 died (5.57%). 75 (6.5%) patients had some kind of residual deformity or disability. Conclusion: The high incidence of pediatric trauma on roads and falls indicate the need for more supervision during playing and identification of specific risk factors for these injuries in our setting. This study shows that these epidemiological parameters could be a useful tool to identify burden and research priorities for specific type of injuries. A comprehensive trauma registry in our set up seems to be important for formulating policies to reduce pediatric trauma burden.